2017
DOI: 10.1007/s11060-017-2422-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of ABCG2 and XIAP in glioblastomas

Abstract: Despite multimodal treatment that includes surgery, radiation and chemotherapy, virtually all glioblastomas (GBM) recur, indicating that these interventions are insufficient to eradicate all malignant cells. To identify potential new therapeutic targets in GBMs, we examined the expression and function of proteins that are associated with therapy resistance and cancer cell survival. We measured the expression of eight such proteins in 50 GBM samples by immunohistochemistry and analyzed patient survival. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 37 publications
1
27
0
1
Order By: Relevance
“…X‐linked inhibitor of apoptosis (XIAP), the anti‐apoptotic protein, hinders chemotherapy‐induced apoptosis by the reduction of caspase‐3, ‐7 and ‐9 activation . Glioblastoma patients with high XIAP expression had worse survival rates than those with low XIAP expression . As shown in Figures and , XIAP expression was significantly decreased by imipramine in glioblastoma U87 MG and GBM‐8401 cells.…”
Section: Discussionmentioning
confidence: 93%
“…X‐linked inhibitor of apoptosis (XIAP), the anti‐apoptotic protein, hinders chemotherapy‐induced apoptosis by the reduction of caspase‐3, ‐7 and ‐9 activation . Glioblastoma patients with high XIAP expression had worse survival rates than those with low XIAP expression . As shown in Figures and , XIAP expression was significantly decreased by imipramine in glioblastoma U87 MG and GBM‐8401 cells.…”
Section: Discussionmentioning
confidence: 93%
“…XIAP was found to regulate PTEN activity and compartmentalization through its mono- and polyubiquitination in HEK-293-T, MCF-7, and HeLa cells ( 28 ). Emery IF et al utilized 50 GB samples and reported that XIAP overexpression was involved in GSCs development and XIAP could be a useful indicator of patient survival ( 152 ). Lopez, et al showed that XIAP knockdown/inhibitors sensitize GB to temozolomide and other chemotherapy drugs ( 153 ).…”
Section: Aberrant Ubiquitination Disrupts Homeostatic Balance Of Ptenmentioning
confidence: 99%
“…Recently, it have been demonstrated that there were higher expressions of XIAP and Bcl‐2 in the glioblastoma samples than that of normal brain samples that can be allowing the development of new target therapy strategies among GBM patients . XIAP mediates apoptosis resistance and XIAP is a potent inhibitor of cell death that involved the inhibition of specific caspases . Our results indicated BITC decreased the levels of MCL1 and XIAP that may be one of the mechanisms for reduced tumor volumes and weight in xenograft mice model.…”
Section: Discussionmentioning
confidence: 53%
“…XIAP is a protein whose activity mediates chemotherapy resistance and apoptosis resistance . Recently, it have been demonstrated that there were higher expressions of XIAP and Bcl‐2 in the glioblastoma samples than that of normal brain samples that can be allowing the development of new target therapy strategies among GBM patients . XIAP mediates apoptosis resistance and XIAP is a potent inhibitor of cell death that involved the inhibition of specific caspases .…”
Section: Discussionmentioning
confidence: 99%